Effect of gambir extract Uncaria gambierRoxb. on fetal of pregnant mice induced by alcohol - A, Almahdy (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2010)
Anomaly in the fetus of mice may induced by the present of oxidative stress on the dam during gestation. Alcohol is a potential substance that able to generate the oxidative stress. Antioxidant theoretically should reduce the above process. Gambir extract is a notorious non toxic herbal which rich of antioxidants. This study aims to see whether the oxidative stress in pregnant mice induced by alcohol could be suppressed with gambir extracts. The results showed that administration of gambir extract to thepregnant dam of mice after been induced by alcohol during gestation, reduced the presence of a thrombus on the pup.Key words: Gambir extract, ethanol, teratogen, mice